Oxoplastics, Bioplastics, and their Potential of Microplastics Generation (Case Study: Indonesia) - Firdha Cahya Alam (Sriwijaya Journal of Environment, 2022)
Plastics are still becoming popular topic in public news. This was initiated by some sea-animals that was trapped by plastic straws, plastic fishing net, and the other plastic packaging. This plastics problem are starting to become global issue and escalate the awareness of people to reduce the plastics use. Some campaign of reducing plastic use are varied, such as starting a zero-waste lifestyle, banning plastics bags, and the other solution is using degradable plastics. Unfortunately, some of the degradable plastics just become a label and only part of greenwashing product. With the increasing issue of microplastics, this degradable plastics is still seen to be skeptical from some academic perspective. The other solution that becoming popular is using biodegradable plastics or bioplastics. This bioplastic is said to be a better option because it is made from natural substrate that easily degrade, edible, and claimed to be safer for the environment. But this claim is still need further research and also standardization of biodegradability definition. This review will provide about the definition of biodegradable plastics, the differences between oxoplastic and bioplastics; the implementation of bioplastic or oxoplastic product in Indonesia, and issue related to microplastic generation